Multiscale Evolutionary Dynamics of Host-Associated Microbiomes - Ferreiro, Aura; Crook, Nathan; Gasparrini, Andrew J.; Dantas, Gautam (Cell, 2018)
The composite members of the microbiota face a range of selective pressures and must adapt to persist in the host. We highlight recent work characterizing the evolution and transfer of genetic information across nested scales of host-associated microbiota, which enable resilience to biotic and abiotic perturbations. At the strain level, we consider the preservation and diversification of adaptive information in progeny lineages. At the community level, we consider genetic exchange between distinct microbes in the ecosystem. Finally, we frame microbiomes as open systems subject to acquisition of novel information from foreign ecosystems through invasion by outsider microbes. This review considers mutations in individual microbes, community gene transfer processes and cross-ecosystem information sharing as distinct influences impacting host-associated microbial adaptation in vivo.